2018
DOI: 10.1016/j.pedneo.2017.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Renal replacement therapy in the neonatal intensive care unit

Abstract: Our study findings reveal RRT to be feasible, even in preterm neonates with low birth weight. CRRT had a higher efficacy level, particularly in neonates with IEM, and the complications encountered were transient and correctable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 27 publications
0
21
1
Order By: Relevance
“…The results of this study showed that the effect and prognosis of CRRT were similar among children of 3.0–10.0 kg or in elder children. It can be seen that CRRT may significantly improve the clinical outcome and prognosis of AKI in low birth weight infants [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study showed that the effect and prognosis of CRRT were similar among children of 3.0–10.0 kg or in elder children. It can be seen that CRRT may significantly improve the clinical outcome and prognosis of AKI in low birth weight infants [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…These include vascular access, bleeding complications, and lack of neonate-specific devices. An adequately-sized central venous access is needed to accommodate adequate blood flow rates and a CRRT machine meant for neonates should be adapted [ 25 , 26 ]. A few studies have reported the use of CRRT in the NICU [ 25 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…An adequately-sized central venous access is needed to accommodate adequate blood flow rates and a CRRT machine meant for neonates should be adapted [ 25 , 26 ]. A few studies have reported the use of CRRT in the NICU [ 25 27 ]. Although CRRT practices can be modified to fit the needs of neonates including preterms, there is a need for a device designed specifically for this population [ 25 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased ammonia levels causing neurological symptoms can be detected in various inborn errors of metabolism (IEM). CRRT has been reported as an effective way of ammonia removal and reversal of neurological symptoms [9].…”
Section: Introductionmentioning
confidence: 99%